Reliability & life testing handbook. Volume 2 - Kececioglu, Dimitri (DEStech Publications, 2002)
This volume includes the binomial tests of comparison and up-to-date information on Accept-Reject Tests, the Sequential Probability Ratio Test, Bayesian MTBF and Reliability Demonstration Tests, as well as other very important accelerated tests such as Arrhenius, Eyring, Bazovsky, and Inverse Power Law.